CARBONDIOXIDE SINK ABILITY OF 15 PLANT SPECIES COLLECTION IN BOGOR BOTANICAL GARDEN - Masfiro Lailati Lailati (Pusbindiklat - LIPI, 2013)
The increasing number of industries and motor vehicles has an impact in the increased concentration of carbondioxide in the atmospheree. This has been causing green house effects (global warming). Therefore, the availability is essential for absorbing carbondioxide in large capacity, both in forest areas as well as in large cities. The objective of this research is to measure carbondioxide sink ability of fifteen (15) species of local plants and to determine the effective in absorbing carbondioxide. Leaf of local plants collection samples were collected from the Bogor Botanical Garden. Carbohydrate analysis was done in the Laboratory Biokimia BB-BIOGEN Bogor, while stomata examination was done in Laboratory Kayu Solid IPB. The data obtained were analyized using carbohydrate mole comparation and linear regression. The highest sink ability was found for canary (12,638.453 g/hour) and the lowest was found for sandalwood (1.379 g/hour). Sink ability of the other species ranged between 131.244 g/hour and 11,461.506 g/hour.